Optimalisasi Layanan Informasi Dan Administrasi Sanggar Kegiatan Belajar Ponorogo Kepada Masyarakat - Nurfitri, Khoiru; Zulkarnain, Ismail Abdurrozzaq; N, Nurwanto (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The management of data at UPT Sanggar Kegiatan Belajar Ponorogo is still done manually. Given the current era of globalization, many companies/agencies have used computerized systems to manage data in order to simplify and speed up work. Based on the description above, we carry out community service activities in the form of developing and applying a computerized data management system in the Ponorogo'SKB. The system that we built is an information and administration system. Based on a computerized system capable of processing data quickly and accurately as well as being able to store and display transaction data related to administration. The method we use in this activity is to provide a computerized system and directly conduct training as well as assistance in operating the system. We hope that by developing this administrative information system the Ponorogo community can more easily access information about the SKB Ponorogo and make it easier to manage the administration of the SKB better and faster. Until now, our activities have reached the stage of training in the operation of the information system for all admins in SKB Ponorogo.